Mechanism of the Dehydrogenative Phenothiazination of Phenols - Goswami, Monalisa; Konkel, Alexander; Rahimi, Maryam; Louillat‐Habermeyer, Marie‐Laure; Kelm, Harald; Jin, Rongwei; de Bruin, Bas; Patureau, Frederic W. (Chemistry : a European journal, 2018)
The straightforward capture of oxidized phenothiazines with phenols under aerobic conditions represents a unique cross‐dehydrogenative C−N bond‐forming reaction in terms of operational simplicity. The mechanism of this cross‐dehydrogenative N‐arylation of phenothiazines with phenols has been the object of debate, particularly regarding the order in which the substrates are oxidized and their potentially radical or cationic nature. Understanding the selective reactivity of phenols for oxidized phenothiazines is one of the key objectives of this study. The reaction mechanism is investigated in detail by utilizing electron paramagnetic resonance spectroscopy, cyclic voltammetry, radical trap experiments, kinetic isotope effects, and solvent effects. Finally, the key reaction steps are calculated by using density functional theory (DFT) and broken‐symmetry open‐shell singlet DFT methods to unravel a unique biradical mechanism for the oxidative phenothiazination of phenols. Together in perfect harmony: The mechanism of the straightforward capture of oxidized phenothiazines with phenols is investigated by electron paramagnetic resonance spectroscopy, cyclic voltammetry, radical‐trapping experiments, kinetic isotope effects, and solvent effects. The key reaction steps are calculated by using DFT and broken‐symmetry open‐shell singlet DFT methods to unravel a unique biradical mechanism for the oxidative phenothiazination of phenols.